(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
This study was a clinic-based cross-sectional survey that was incorporated with quantitative and qualitative data collection. Information on sociodemographic characteristics of the caregivers was assessed with the aid of a validated semi-structured questionnaire. Weight, oedema, and Mid up Arm Circumference (MAUC) of the children were measured weekly to monitor the progress of the programme. This study shows that 8(26.67%) of the caregivers were aged 21 – 25 years and 26 - 30 years each, while 7 (23.33%) were 18 - 20 years of age, only 1(3.33%) of the caregiver was above 40 years. The mean age of the respondents was 27 years. Educational status shows that 17(56.67%) of the caregivers attended Secondary school as the highest level of education, 5(16.67%) had no formal education while only 1 attended tertiary institution. Occupation wise, 36.67% (n=11) of the caregivers were Artisan/Skilled Worker, followed by 10(33.33%) who were housewives. The result of the MUAC of the SAM children for 8 weeks shows that the mean value for the first week was 9.73. The boosters of the programme show 76.7% of RUTF, 10% of porridge beans, tofu and turn brown. The cost of transportation and distance as barriers was 60% and 26.7% respectively. The performance indicators show 77.8% cure rate, 8% default rate, 2.7% death rate and no recovery rate was 11.1%. Geographic coverage is 5.8% which when compared with the percentage standard is alarming. Therefore, geographic coverage in this study site was low and this would translate into low program effectiveness